Transformation of Home Environments in Pandemic: the Concept of “Life Fits Into Room” in the New Normal - BİRER, EMEL; HASGÜL, ESİN; CAN, EREN (Emerald Group Holdings Ltd., 2022)
Purpose: Pandemic process has led re-questioning home environments within adaptations of new activities inside due to the restriction of outdoor usage. This paper aims to reveal spatial transformations carried out through the time spent at home during the COVID-19 pandemic. Design/methodology/approach: A qualitative study is carried out based on Garfinkel’s (1961) ethnomethodology method (documentary method of interpretation). Analysis focused on the first month of pandemic in which urgent adaptations and solutions produced at home, and the situation in last two weeks of pandemic is analyzed within a control group and comparisons were made. Perec’s (1974) statement of “a user's manual” is used as a checklist of time-space-activity observations proposed on “mondayness, tuesdayness, wednesdayness, thursdayness, fridayness, saturdayness and sundayness.” Instead of daily period, activities performed on a weekly scale were recorded and time-dependent shifts of functions were revealed. Findings: Findings introduced new discussion topics to examine dwelling spaces in “new normal.” Comparisons indicate that hypothesis of gathering all activities in room in terms of “life fits into room” concept is directed through rapid spatial behaviors in daily life as primary adaptation. Research limitations/implications: Although pandemic process continues after study, analysis of first four weeks are accepted as the period of rapid change and compared by last two weeks of pandemic. Originality/value: Pandemic indicators proposed in study brings along that there is little information on the subject in literature. Socio-spatial findings address the examinations of spatial transformations into pandemic adaptation. © 2021, Emerald Publishing Limited.
Keywords: Daily Life; Ethnomethodology; Home; Pandemic Adaptation; Spatial Behavior